Failure and stability analysis of deep soft rock roadways based on true triaxial geomechanical model tests. (July 2022) - Zhu, Qingwen; Li, Tingchun; Du, Yiteng; Zhang, Hao; Ran, Jinlin; Li, Weiteng; Zhang, Shilin
Highlights: Study the deformation and failure law of deep soft rock roadway excavation. Enabled the alternate construction of roadway excavation and support in model test. Study a prestress model bolt and form a collaborative system of bolt-mesh-shotcrete. Analyze the stress and deformation characteristics of the interior surrounding rock. Research the bolt force and the contact stress between surrounding rock and lining. Abstract: The deformation and failure of deep soft rock roadways become more prominent. In this paper, two true triaxial model tests were carried out to investigate the deformation and failure law of deep soft rock roadway excavation and the stability characteristics of the surrounding rock after the support. The surrounding rock stress and roadway deformation characteristics can be divided into three stages: advance influence, rapid change and stability. The deformation and failure sequence during the excavation process of the model roadway is "vault → sidewalls → arch springing → roof collapse". Roof stability is the top priority. After the supporting structure is applied, the surrounding rock stress increases obviously and the roadway deformation decreases. The model test results are verified through field monitoring, and the key deformation parts of the deep soft rock roadway and the characteristics of the supporting structure force are clarified, which can provide reference for later research.